PSIKOTERAPI QUR’ANI : (Konsep Mindfulness dalam QS. Al-Hadid [57]: 16) - Moh. Wafiq Ulinnuha Ulinnuha; Abu Bakar (Jurnal Al I'jaz, 2026)
Mental health is one of the crucial issues faced by modern society. One of the therapies that has developed in contemporary psychotherapy is mindfulness, a full-awareness-based therapy used to manage psychological conditions. This article aims to examine the concept of mindfulness contained in the Qur’an, particularly QS. Al-Hadid :16, considering that many Qur’anic verses relate to psychological aspects, especially the dimension of awareness. This study employs a qualitative method with a descriptive-analytical approach based on library research. The findings indicate that QS. Al-Hadid :16 encompasses the concept of mindfulness therapy by emphasizing the spiritual dimension as its primary foundation. The verse includes stages of awareness that can be adopted as a framework for psycho-spiritual therapy, namely: (1) introspection (al-muh{asabah), (2) awareness of divine supervision (al-muraqabah), (3) experiencing the majesty of the Divine (al-khusyu’), (4) contemplation of God’s creation (al-tafakkur), and (5) integrity as a form of harmony between thought, speech, and action. This Qur’anic concept of mindfulness functions as a source of inner tranquility as well as an alternative approach to addressing modern mental health problems. Thus, this study contributes to enriching Islamic psychology research and offers an integration between contemporary psychotherapeutic approaches and Qur’anic values.